2021
DOI: 10.3390/encyclopedia1040096
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysteroids

Abstract: Ecdysteroid: member of a class of polyhydroxylated steroids found in invertebrate animals (zooecdysteroids; moulting hormones), plants (phytoecdysteroids) and fungi (mycoecdysteroids). Over 500 structural analogues are currently known. Biosynthetically, they derive from C27-, C28- or C29-sterols. The most frequently encountered analogue (in arthropods and plants) is 20-hydroxyecdysone (2β,3β,14α, 20R,22R,25-hexahydroxycholest-7-en-6-one). In arthropods, ecdysteroids occur universally and regulate development b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 180 publications
(178 reference statements)
0
8
1
Order By: Relevance
“…Nevertheless, it can currently be assumed that chronic FEN application does not influence bench press performance. Consequently, the results are in contrast to the effect on lower body performance and other phytosteroids [44,45].…”
Section: Rm Bench Presscontrasting
confidence: 59%
“…Nevertheless, it can currently be assumed that chronic FEN application does not influence bench press performance. Consequently, the results are in contrast to the effect on lower body performance and other phytosteroids [44,45].…”
Section: Rm Bench Presscontrasting
confidence: 59%
“…In all naturally arising ecdysteroids, the A/B ring junction is generally cis and hardly ever trans , whereas the B/C and C/D ring junctions are always trans. In the NOESY spectrum of 1 (Figure ), the strong correlations between H-2/H-9 supported a cis A/B ring junction. The α-configurations of H-2 and H-3 could be confirmed by the large and small coupling constants ( 3 J H‑1β/H‑2 = 12.1 Hz and 3 J H‑2/H‑3 = 3.1 Hz), respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, Xavier et al (2016) reported the phytoecdysteroid fraction of C. dentata and N. cordifolia with the occurrence of tannins, steroids, phenolic compounds and terpenoids. Among the pteridophytes, Cheilanthes tenufolia, Polypodium vulgare (Lafont et al, 2021), Pteridium aquilinum, Seratula tinctora, Cheilanthes farinosa (Rajkumar et al, 2000), Christella parasitica, Pteridium aquilinum and Hemionitis arifolia (Sahayaraj and Selvaraj, 2013) were reported to contain phytoecdysones. UV-Visible spectrophotometry analysis of phytochemicals in the phytoecdysteroid fraction P. calomelanos showed six prominent peaks at the wavelength ranging between 326.5nm -666nm.…”
Section: Survival and Development Of S Lituramentioning
confidence: 99%
“…Various authors reported the absorption spectrum of different phytochemicals that include steroids (200-400nm) and polyphenols (240-650nm) (Zahari et al, 2016). UV absorbance of 20 -E (ecdysteroid analogue) recorded at 242nm and 310nm (Lafont et al, 2021). Raimana et al (2008) reported a typical ecdysteroid spectrum with a maximum wavelength of 242nm and two unusual peaks at 294 and 317nm indicated the presence of an aromatic conjugating moiety.…”
Section: Survival and Development Of S Lituramentioning
confidence: 99%